Análise espaço-temporal do uso e cobertura da terra no Município de Benevides, Pa - MACEDO, Acsa Marilha Souza de (2023)
This paper aims to present the results achieved by research on land use and land cover in the municipality of Benevides (PA), through data produced on the MapBiomas platform. It was used data from the time series 1985 to 2020 of land use and coverage made available by the MapBiomas project, geoprocessing and remote sensing techniques and QGIS 3.22 software, thus it was possible to spatialize the use and coverage of the land of the municipality and relate it to the territorial dynamics of the period. The result of the research indicates that the process of occupation of Benevides occurred from its road networks, river-rail-road, and in this process of land occupation changes in space were intense with appropriation of riverbanks for construction of the port, reduction of approximately 20% of its primary forest composition, for construction of road networks, increase of 13% of agricultural areas and 5% of non-vegetated areas corresponding to the formation of urban areas. An accelerated process of urban growth has begun, without planning, linked to 1the insertion of the city to the Metropolitan Region of Belém. The transformations in the spaces of Benevides follow the modernizing logic of capitalism which is to advance rapidly over the territory and establish new territorialities of domination. The result of the research indicates that further studies on the environmental dynamics of the areas of influence of major highway projects for the Amazon are fundamental.